I will tell no war stories : what our fathers left unsaid about World War II - Mansfield, Howard (Lyons Press, 2024)
"I Will Tell No War Stories is about undoing the forgetting in a family and in a society that has hidden the horrors and cataclysm of a world at war. Some part of that forgetting was necessary for the veterans, otherwise how could they come home, how could they find peace?"--